2019
DOI: 10.1002/jssc.201900700
|View full text |Cite
|
Sign up to set email alerts
|

An overview on enrichment methods for cell surface proteome profiling

Abstract: Cell surface proteins are essential for many important biological processes, including cell–cell interactions, signal transduction, and molecular transportation. With the characteristics of low abundance, high hydrophobicity, and high heterogeneity, it is difficult to get a comprehensive view of cell surface proteome by direct analysis. Thus, it is important to selectively enrich the cell surface proteins before liquid chromatography with mass spectrometry analysis. In recent years, a variety of enrichment met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 239 publications
0
38
0
Order By: Relevance
“…Analyzing glycoproteomes from whole-cell lysate generates confounding artifacts that complicate determination of what glycoforms are biologically relevant and present on the cell surface. Several approaches have been developed to label cell-surface glycoproteins on live cells, prior to cell lysis and protein extraction ( 306 , 307 ). One variation functions similarly to the approaches above: sialic acids are oxidized on live cells via mild periodate treatment, and aldehyde-containing sialylated glycopeptides are captured on hydrazide beads.…”
Section: Chemical Coupling Strategiesmentioning
confidence: 99%
“…Analyzing glycoproteomes from whole-cell lysate generates confounding artifacts that complicate determination of what glycoforms are biologically relevant and present on the cell surface. Several approaches have been developed to label cell-surface glycoproteins on live cells, prior to cell lysis and protein extraction ( 306 , 307 ). One variation functions similarly to the approaches above: sialic acids are oxidized on live cells via mild periodate treatment, and aldehyde-containing sialylated glycopeptides are captured on hydrazide beads.…”
Section: Chemical Coupling Strategiesmentioning
confidence: 99%
“…Nevertheless, an important determinant would be a complete knowledge of the surfaceome, i.e., the entirety of all proteins on the cell surface [99]. Experimental approaches for this involve specific labeling of surface proteins (e.g., via biotinylation) and their subsequent enrichment, followed by their identification by mass spectrometry [100]. A single study has reported such data for tachyzoites of T. gondii [101] (similar data for bradyzoites and sporozoites are not available).…”
Section: What Makes a Protein A Good Antigen?mentioning
confidence: 99%
“…PM proteins are typically of low abundance and underrepresented in proteomic samples. It is therefore necessary to selectively enrich for PM proteins prior to proteolysis and MS. Methods for this purpose include those that isolate PM proteins by utilizing their physicochemical properties (size, charge, or hydrophobicity), use bimolecular affinity interaction with a lectin or antibody, or use chemical covalent coupling to the side groups of surface exposed proteins (86). Plasma membrane profiling (PMP) involves the selective oxidation and aminooxy-biotinylation of sialylated PM glycoproteins, followed by affinity purification with high capacity streptavidin (87, 88) (Figure 2b).…”
Section: Changes In Spatial Organizationmentioning
confidence: 99%